Analisis Motif dengan Teknik Sashiko pada Blazer Dari Kain Sutra Taffeta Sumber Ide Bunga Lagosi - Andi Nurliana; Rosmiaty Rosmiaty; Rika Riwayani (HomeEC, 2021)
This research is an experimental study that aims to determine the design of the blazer, the processof making a blazer, the process and method of making the sashiko technique, the opinion of the researcher onthe results of the blazer using the sashiko technique. Data collection techniques used are FGD, documentation,and questionnaires. The data analysis used is descriptive quantitative analysis with presentation and Likert scale.The results of the research are based on the objectives, namely the design of a blazer in the form of an Asilhouette with a lapel collar and a paspoile pocket and two lagosi motifs, designing and then making a patternthen the process of making a blazer, making a pattern pattern and then tracing the motif then the process ofmaking a sashiko technique motif, the results of the panelist test using 3 indicators namely productspecifications, sashiko techniques, and product results The assessment shows the percentage of the average valueof the total number of items as much as 85.5% categorized as very good with the overall acquisition liking both interms of color, design, size, shape, motif, suitability of materials and products, and overall appearance.